Ultrasonographic Evaluation of Gastric Content and Volume in Pediatric Patients Undergoing Elective Surgery: A Prospective Observational Study - Asiye Demirel; Şeyda Efsun Özgünay; Şermin Eminoğlu; Ayşe Neslihan Balkaya; Tuğba Onur; Nermin Kılıçarslan; Mehmet Gamlı (MDPI AG, 2023)
Anesthesia-related complications, such as pulmonary aspiration of gastric contents, occur in approximately 0.02-0.1% of elective pediatric surgeries. Aspiration risk can be reliably assessed by ultrasound examination of the gastric antrum, making it an essential non-invasive bedside tool. In this prospective observational study, since most of our patients are immigrants and have communication problems, we wanted to investigate gastric contents and the occurrence of "high risk stomach" in children undergoing elective surgery for the possibility of pulmonary aspiration, even if the children and/or parents reported their last oral intake time. This risk is defined by ultrasound findings of solid content in the antrum and/or a calculated gastric volume exceeding 1.25 mL/kg. Children aged 2-18 were included in the study. Both supine and right lateral decubitus (RLD) ultrasound examinations were performed on the antrum before surgery. Using a qualitative grading scale from 0 to 2, we evaluated the gastric fluid content. The cross-sectional area (CSA) of the antrum was measured in the RLD position, aiding the calculation of the gastric fluid volume according to an established formula by Perlas. Ultrasound measurements of 97 children were evaluated. The median fasting duration was 4 h for liquids and 9 h for thick liquids and solids. Solid content was absent in all the children. Five children (5.2%) exhibited a grade 2 antrum, implying that fluid content was visible in both the supine and RLD positions. The median antral CSA in the RLD was 2.36 cm2, with a median gastric volume of 0.46 mL/kg. For patients with a grade 0 antrum, a moderate and positive correlation was observed between the antral CSA and BMI, and a strong and positive correlation was evident between the antral CSA and age, similar to a grade 1 antrum. Only a single child (1%) had a potentially elevated risk of aspiration of gastric contents. Hence, the occurrence of a "high risk stomach" was 1% (95% confidence interval: 0.1-4.7%) and is consistent with the literature. As a necessary precaution, we propose the regular use of ultrasound evaluations of gastric contents, given their non-invasive, bedside-friendly, and straightforward implementation, for identifying risks when fasting times are uncertain and for ruling out unknown risk factors in each potential patient.